2015
DOI: 10.1111/jvp.12264
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous absorption of chemicals: developing an understanding for the treatment of disease in frogs

Abstract: The permeable nature of frog skin presents an alternative route for the delivery of therapeutic chemicals to treat disease in frogs. However, although therapeutic chemicals are often topically applied to the skin of frogs, their pharmacokinetics have rarely been reported. To provide evidence to guide both candidate drug and formulation selection, we highlight factors expected to influence percutaneous absorption through frog skin, including the anatomy and physiology of the skin and the physicochemical propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 83 publications
1
10
0
Order By: Relevance
“…Because lipophilicity is likely to be a primary influence on transdermal absorption through frog skin (Llewelyn et al ), the chemicals included in the present study were selected to investigate the impact of increasing lipophilicity on transdermal absorption. In contrast to the findings in L. caerulea , which showed a parabolic relationship between logFlux and log P for dorsal absorption and a linear relationship for ventral absorption (Llewelyn et al ), the impact of lipophilicity on flux was consistent between skin regions in R. marina , demonstrating a decline with increasing lipophilicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because lipophilicity is likely to be a primary influence on transdermal absorption through frog skin (Llewelyn et al ), the chemicals included in the present study were selected to investigate the impact of increasing lipophilicity on transdermal absorption. In contrast to the findings in L. caerulea , which showed a parabolic relationship between logFlux and log P for dorsal absorption and a linear relationship for ventral absorption (Llewelyn et al ), the impact of lipophilicity on flux was consistent between skin regions in R. marina , demonstrating a decline with increasing lipophilicity.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is well established that the physicochemical properties of a chemical will influence its rate and extent of absorption through mammalian skin, there is scant evidence as to how these properties influence transdermal pharmacokinetics through frog skin. Llewelyn et al () reviewed the physicochemical and skin properties that are likely to influence transdermal pharmacokinetics through frog skin, based on known frog skin physiology. Reviewing the reported outcomes for transdermal treatments and in vitro pharmacokinetic experiments in frog skin, they concluded that the relative lipophilicity of a chemical being applied to the skin, the thickness of the skin, and the skin's relative vascularization are likely to influence absorption kinetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Main determinants of dermal absorption are indicated to be molecular size (expressed as molecular volume or weight) and hydrophobicity (expressed by log P O/W ). Basically, in mammalian skin low molecular weight and high lipophilicity (up to a log P O/W of 3) lead to higher permeability coefficients [ 17 , 40 ]. In contrast to mammalian skin, the skin of X. laevis is characterized by a superficial mucus film.…”
Section: Discussionmentioning
confidence: 99%
“…Quaranta et al showed frog skin permeability being linearly and positively correlated to log P O/W (logarithm of octanol–water partition coefficient) of the applied substance, while log MW (logarithm of the molecular weight) did not predict dermal absorption [ 16 ]. Further, there is evidence from the literature that amphibian skin is permeable even to large molecules (>500 Da) and to a broader range of log P O/W (−4 to +6) compared to mammalian skin [ 17 ]. Besides physico-chemical properties of a penetrant, the other important factor influencing dermal absorption is the skin structure itself, which may differ to some extent between species adapted to different habitats, but also within one animal between different skin sites such as dorsal skin, ventral skin, or the so-called pelvic patch as a skin area specialized for fast water uptake [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%